Is white copra more attractive than black copra? Comparative study of marketing margin and farmer's share in Southeast Sulawesi - Campina Illa Prihantini; Yusriani Rizqy; Nursalam Nursalam; Yuli Purbaningsih; Dennis Mark Onuigbo (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2022)
Coconut (Cocos nucifera L.) is one of the plantation commodities that has an important role in the economy of coastal communities in Indonesia. Based on data released by the Central Statistics Agency, in 2020 Bombana Regency has a number of coconut plantations covering an area of 14,550 ha, and about 23 percent of which are located in Poleang District so the sub-district has the potential to produce copra production. This study aims to analyze the black and white copra marketing pattern. The analysis used is marketing channel analysis, marketing margin analysis and farmer's share, and marketing function analysis. The data used in this study are primary data obtained through interviews with respondents and secondary data obtained from relevant agencies, including the results of other studies in the form of scientific journals. The results showed that there was one copra marketing channel in Poleang District which consisted of three marketing institutions. The farmer's share analysis showed that the value received by farmers on black copra was 82,14% while that received on white copra was 78,66%. The analysis of the marketing function shows that each marketing agency has performed its marketing function well.